Pelatihan Mindfulness Untuk Meningkatkan Kualitas Hidup Pada Orang Dengan HIV/AIDS (ODHA) - Ramadhani, Rahma Putri; Nashori, Fuad; Kumolohadi, Retno (Al-Qalb : Jurnal Psikologi Islam, 2021)
Abstract: HIV/AIDS can emerge a number of issues that can lead to the deterioration quality of life to People Living with HIV/AIDS. The problems arising include  the poor physical condition, social pressure and psychological effects on people living with HIV/AIDS. One of the efforts that can be done to improve the quality of life ODHA is through the mindfulness training. Mindfulness is a set of structured activities in the form of mind meditation aimed to train the individual to develop the ability to focus the attention on the existing conditions, events and activities. This research aims to observe the effectiveness of mindfulness training to improve the quality of life to People Living with HIV/AIDS (ODHA). The participants consisted of five people as the subject. The design of this research used was One Group Pre-test Post-test. Intervention was given within two days. The measurement tool used was the  questionnaires of WHOQOL-HIV BREF developed by WHO (2017) that has been adapted into Indonesia Language by Muhammad, Shatri, Djoerban and Abdullah  (2017). Based on the Wilcoxon Signed Rank Test, it was found the value of Z = -2,023 with p = 0,043 meaning that mindfulness training was effective to improve the quality of life PLWHA.